ON SOME ASPECTS OF THE COMPETITIVENES OF GEORGIAN WINE-PRODUCING COMPANIES - Eka Chokheli; Gvantsa Eristavi (Foundations and Trends in Research, 2025)
The Georgian wine industry has gained increasing global recognition due to its unique cultural heritage, indigenous grape varieties, and ancient winemaking traditions, particularly the use of the “Qvevri” method. This paper assesses the competitiveness of Georgian wine producers in the international market and explores strategic development pathways to ensure sustainable growth. Through analysis of export dynamics, market diversification, and internal capabilities, the study identifies key strengths such as differentiated product offerings, rising demand in premium segments, and growing export volumes. However, several systemic challenges remain, including certification barriers for small producers, logistical and regulatory constraints, limited branding and marketing resources, human capital shortages, and geopolitical risks in key markets. The paper proposes strategic recommendations across multiple dimensions—quality management, branding and digital marketing, geographic diversification, innovation and digital transformation, and workforce development. Ultimately, enhancing the global competitiveness of Georgian wine requires a shift from reliance on cultural heritage alone toward evidence-based, future-oriented strategies capable of securing a resilient and prominent position in global wine markets.